ERP Evidence for Inhibitory Control Deficits in Test-Anxious Individuals - Zhang, Wenpei; De Beuckelaer, Alain; Chen, Lirong; Zhou, Renlai (Frontiers in Psychiatry, 2019)
Introduction: Individuals with test anxiety [i.e., high test anxiety (HTA)] always treat tests/examinations as a potential threat. This cognitive mode impairs these individuals’ ability of inhibitory control and leads to a high level of anxiety. However, characterizing aspects of HTA’s impaired inhibitory control ability are unclear and need to be studied. Methods: Forty-six participants were recruited and divided into a HTA (N = 26) and low test anxiety (LTA; i.e., healthy control; N = 20) group. Self-reports (Test Anxiety Scale, State-Trait Anxiety Inventory for negative emotions) were obtained. An emotional Stroop (ES) task and a numerical Stroop (NS) task, causing different types of interferences, were used for assessing the emotional and cognitive aspects of attentional control ability (behavioral data). Event-related brain potentials (ERPs) were registered to further assess processing stages related to different aspects of attentional control ability. Results: Compared with the LTA group, the HTA group has inhibitory control deficits of both emotional (see ERP components P1-P2-N2 and P3) and cognitive (see ERP component P3) interference. Compared with the LTA group, the HTA doesn't have lower accuracy in neither ES nor NS but displays longer reaction times only in ES. Additionally, the HTA group’s ES results also show that (1) the degree of emotional interference indicates the level of an individual’s anxiety, and (2) the ERP component P2 may serve as an index of the level of test anxiety. Conclusion: HTA individuals have extensive inhibitory deficits for both emotional and cognitive aspects; however, impairment impacts more on emotional aspects than on cognitive aspects. Additionally, as compared to NS, the negative impact of more impaired processing stages on task performance is more substantial in ES.